Analisis Jenis Makna Penamaan Objek Wisata Curug di Tasikmalaya (Kajian Semantik) - Aulia Gita Ayuningtyas; Chika Laras Pramestuti; Risqi Sri Mulyati; Aveny Septi Astriani (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to (1) describe the types of meaning that exist in naming waterfall tourist objects and (2) describe the factors behind naming waterfall tourist objects. This study used descriptive qualitative method. The data collection technique in this research uses literature study. The data analysis technique used is a qualitative data analysis technique. Semantics is a branch of linguistics that studies meaning. One of the objects of semantic study is names. Humans can give names to animals, objects, food, and even places to use as identity. Each region has local wisdom that characterizes it, one of which is tourism. Tasikmalaya is famous for its many tourist destinations, one of which is the natural waterfall tourist attraction. The results of this research show that the name of the waterfall tourist attraction in Tasikmalaya has several types of meaning, including lexical meaning, referential meaning, denotative meaning and conceptual meaning. Apart from that, there are several factors behind the naming of waterfall tourist attractions in Tasikmalaya, including the similarity factor, the place of origin factor, the distinctive characteristic factor, and the new naming factor.